(untitled) - Cabin, Robert J. (Washington, 2011)
In this model, practitioners employ the same kind of careful but informal trial-and-error strategy followed by such groups as indigenous peoples and hobbyist mechanics
Keywords: Restoration ecology; Sinh thái phục hồi